Human Metapneumovirus Infection: Pneumonia Risk Factors in Patients With Solid Organ Transplantation and Computed Tomography Findings. Issue 4 (April 2018) - Koo, Hyun Jung; Lee, Han Na; Choi, Sang Ho; Sung, Heungsup; Oh, Sang Young; Shin, So Youn; Kim, Hwa Jung; Do, Kyung-Hyun
Abstract : Background: Human metapneumovirus (HMPV) is a newly detected pathogen that can cause lower respiratory tract disease. Clinical characteristics, computed tomography (CT) findings, and outcomes of HMPV pneumonia in patients with solid organ transplantation (SOT) have not been well demonstrated. Methods: Between January 2010 and February 2016, clinical and imaging findings of 59 patients with SOT (types of organ: kidney, 37; liver, 16; heart, 4; and pancreas and kidney, 2) who had HMPV infection detected in nasopharyngeal or bronchoalveolar lavage by reverse transcription polymerase chain reaction were retrospectively evaluated. Results: Most (90%) of the patients were detected between March and June. In the 59 patients with SOT with upper respiratory tract infection (URI), 29 (49%) progressed to lower respiratory tract disease after a median of 7 days (range, 2-31 days). Coinfection was noted in 39% of the patients. In Cox proportional hazards analysis, low lymphocyte count (⩽0.7 × 10 3 /μL; hazard ratio, 2.24; 95% confidence interval, 1.04-4.85; P = 0.04) and high C-reactive protein (>10 mg/dL; hazard ratio, 2.93; 95% confidence interval, 1.19-7.21; P = 0.02) at URI diagnosis were associated with HMPV pneumonia. On CT, HMPV pneumonia presented as bilateral ill-defined centrilobular nodules, consolidation and ground-glass opacities, whereas lymphadenopathy or effusion is not common. There were no significantly different imaging CT findings between patients with HMPV infection alone and those with coinfection. Conclusions: Human metapneumovirus pneumonias were detected in nearly half of patients with SOT showing URI symptoms with positive HMPV, and low lymphocyte count and high C-reactive protein at URI diagnosis were significant factors associated with HMPV pneumonia. Abstract : This single-center, retrospective analysis describes the risk factors, clinical presentation and outcomes of human metapneumovirus infection detected in nasopharyngeal or bronchoalveolar lavage in 59 recipients of solid organ transplants.